Design and Implementation of Inventory Management Information System at AMIK PGRI Kebumen - Prasongko, Riski (Journal of Intelligent Systems and Information Technology, 2025)
This research aims to design and implement a management information system that facilitates inventory management at AMIK PGRI Kebumen. The issue faced is that the inventory management system is still manual, leading to inefficiencies and potential data errors. This study employs a software development method using the Waterfall model, which includes requirements analysis, system design, implementation, and testing. The result of this research is a web-based inventory management information system that can effectively and efficiently manage inventory data, supporting processes for adding, editing, deleting, and searching inventory data to monitor the condition and status of the inventory. In conclusion, the implementation of this information system successfully improved the efficiency of inventory management at AMIK PGRI Kebumen, reduced data errors, and simplified information access for users. Recommendations for future research include adding stricter data security features and integrating with other existing systems at AMIK PGRI Kebumen.Abstract must contain